Perilaku Ibu dalam Penanganan Kejang Demam pada Anak - Risa Fitriana; Dessie Wanda (Journal of Telenursing (JOTING), 2021)
This study aims to determine the mother's behavior in handling febrile seizures and the factors that influence them. The method used in this research is a literature search from several online databases. The results showed that from the six articles reviewed, the behavior of handling febrile seizures in children was influenced by cultural factors and factors that influenced mothers. Cultural factors include putting something into the child's mouth, shaking the child's body, reciting the Al-Quran and mantras and spitting water on the child's face. The factors that influence the mother's behavior in handling febrile seizures consist of the mother's characteristics, the characteristics of the child, the level of knowledge and attitudes. In conclusion, overall, the article describes the inappropriate behavior of handling febrile seizures. Keywords: Mother, Management of Fever Seizures, Knowledge, Attitude